The non nonprofit : - Rothschild, Steve (Jossey-Bass, 2012)
A top business leader shares the business principles he used to launch both a top company and a thriving nonprofit Nonprofit leaders know that solving pervasive social problems requires passion and creativity as well as tangible results. The Non Nonprofit shares the same business principles that drive the world's best companies, showing how they can (and should) be applied to the realm of nonprofits. Steve Rothschild personally crossed sectors when he left corporate America to found Twin Cities RISE!, a highly successful poverty reduction program. His honest story, and success and missteps, create an essential roadmap for any social venture looking to prove and boost its impact.Distills essential nonprofit principles such as having a clear and appropriate purpose, creating economic value from social benefit, and establishing mutual accountabilityShares successful approaches from innovative organizations such as Grameen Bank, Playworks, Common Ground, Habitat for Humanity, Lumni, Caring Bridge, College Summit and RISE!Draws from the author's success in founding and building Twin Cities RISE!, which trains unemployed Minnesotans for living wage jobs. RISE! serves 1,500 participants each year As insightful as it is inspiring, The Non Nonprofit can help maximize the positive impact of any nonprofit.